Study of maximum flows of project using a Gumbel distribution (Research, Society and Development, 2021)
The calculation of project maximum floods is fundamental for the design and development of hydraulic constructions. Flood forecasting can be estimated, for example, by applying the calculation of a project flood by extrapolating historical data to critical conditions. Thus, to avoid risks of collapse in hydraulic constructions, it is essential to use specialized statistical distributions to perform the calculations of flows of spillways project. The Gumbel distribution is one of the most widely used probability distribution functions for extreme values in hydrological studies, in which the parameters considered in the analysis are the flow and return period. The Gumbel distribution is one of the most widely used probability distribution functions for extreme values in hydrological studies, in which the parameters considered in the analysis are the flow and return period. In this research work, a Gumbel distribution was used to analyze the data of the maximum flows of a historical series of the Tabajara station, of the Ji-Paraná river, located in the city of Machadinho d’Oeste – RO. The data studied were collected between 1978 and 2015.